TRAINING FOR LEGAL PRACTICE – TOWARDS EFFECTIVE TEACHING METHODOLOGIES FOR PROCEDURAL LAW MODULES - M A (Riette) du Plessis; Marc Welgemoed (Obiter, 2022)
Procedural laws play an important role in legal practice through their use in the enforcement of the substantive rights of members of the public. Civil procedure, criminal procedure, and the law of evidence are the building blocks whereby matters are presented in court. Legal representatives, representing members of the public, should therefore be skilled and professionally trained in procedural laws. Due to their importance, students should not only have a thorough and foundational theoretical knowledge of procedural laws, but also the necessary practical skills in applying their knowledge to practical scenarios, which should be instilled as part of the teaching of procedural modules. The inherent methodological content of conventional teaching methodologies applied when teaching procedural law modules, i.e., the Socratic and case dialogue methodologies, however, prove to be inadequate in transferring the required skills and practical training. Several constituent parties in the legal profession, including academics, legal practitioners, and presiding officers, have remarked that law students, upon graduation, lack the necessary skills, ingenuity, and practical knowledge to make a good start in legal practice. It furthermore appears that university law faculties are generally not willing to train law students for practice. There is also the necessity for the development of identified essential skills required of competent legal practitioners. The continuous development of these skills in the teaching and practical application of procedural laws afford students the ability to advance future client representation professionally and confidently. Cultural, social and human elements should form part of the teaching and learning of procedural law modules, which will create an important awareness among students that, when working with clients in legal practice, they are attending to the rights and interests of human beings who may be of different races and cultures. This will further develop students’ identities and values as professionals which include not only being responsible to individual clients, but also contributing services to the community. In developing the required identified skills, students will not only be able to apply technical legal procedures, but also learn how to assist clients more cost-effectively. By employing the Clinical Legal Education methodology in tandem with conventional lecture methodologies, students are introduced to the practical application of procedural laws, honing both their practical and intellectual skills. Application suggestions include tutorial sessions, mock trials, and reflective assignments. This article evaluates the efficacy of the current teaching methodologies applied in teaching procedural laws toward imparting students with the required practical skills. It recommends the development of procedural law modules by introducing applied practical skills to enable students to enter legal practice after graduation as more rounded and skilled future legal practitioners.